The Nišava river water quality as the indicator of the sustainable development of the city of Niš - Branković Saša (Spatium, 2007)
The Nišava river has a great importance for the sustainable development of the city of Niš. From the Mediana spring, which is on the bank of the Nišava, the city of Niš satisfies around 30% of its water demand. The aim of this paper is to, on the basis of the analysis of several tens of parameters of water quality; determine whether the Nišava river is a limiting factor to the sustainable development of the city of Niš. For this purpose the data of Public Utility Company Naissus have been used, as it collects daily samples of the Nišava river water. The number of conducted analyses, depending on the water quality parameters, varies from 1 to 1,240. The obtained results, which have been presented in detail in the paper, indicate that a great majority of analyses, of almost all the water quality parameters, is within predicted range. At the end of the paper, certain measures have been proposed, which should contribute to the sustainable development of Niš in this field. .